2019
DOI: 10.1097/cmr.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of glucose transporters in melanocytic lesions

Abstract: We have previously reported increased glucose transporter 1 (GLUT1) expression in melanoma compared to benign nevi, associated with a significantly lower survival rate. GLUT1 upregulation was highly specific for distinguishing melanoma from benign nevi, yet poorly sensitive, likely because of expression of other GLUT isoforms. The purpose of this study was to evaluate GLUT2 and GLUT3, as melanoma biomarkers. A tissue microarray, consisting of 91 primary melanomas, 18 melanoma metastases, and 56 nevi, was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Upregulation of glucose transporter‐1 (Glut‐1), the most common human glucose transporter, contributes to an enhanced glucose metabolism in rapidly proliferating tumour cells 3,11 . Several studies have examined Glut‐1 expression in melanocytic nevi and melanoma as well as in non‐melanoma skin cancer 3,12‐14 . However, there is only one immunohistochemical study on record that has analysed Glut‐1 expression in MCC 15 …”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of glucose transporter‐1 (Glut‐1), the most common human glucose transporter, contributes to an enhanced glucose metabolism in rapidly proliferating tumour cells 3,11 . Several studies have examined Glut‐1 expression in melanocytic nevi and melanoma as well as in non‐melanoma skin cancer 3,12‐14 . However, there is only one immunohistochemical study on record that has analysed Glut‐1 expression in MCC 15 …”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the authors demonstrated that GLUT1 expression was correlated with shorter 10-year disease-free survival, relapse-free survival and shorter metastasis-free survival (MFS) [25]. Various other authors [22,[26][27][28][29] have examined these aspects, sometimes with confirmatory but sometimes contradictory results. A very interesting recent paper by Reckzeh et al described the discovery of a powerful inhibitor of glucose transporters 1 and 3, Glutor, that is capable of blocking the uptake of neoplastic cells, blocking the "metabolic plasticity" of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…biomarker. 30 In addition, previous experiments have shown that some GLUTs transport inhibitors have shown good effects in inhibiting tumor growth in mice, making GLUTs a potential target for tumor therapy. 31 Summary, this recent study demonstrates that TCF4 downregulation sensitizes melanoma cells to Vemurafenib through inhibiting GLUT3-mediated glycolysis.…”
Section: Discussionmentioning
confidence: 99%